Factors Influencing the Intention to Adopt Social Technology Driven Based on Marketing According to Generational Theory in Educational Organizations - Zakaria, Saif Khalid (Journal of Technology Management and Business, 2024)
The main objective of this study is to research and investigate the trend and intention of educational organizations towards using technology and social media by employing marketing according to generational theory to enhance the performance of organizations in the workplace. This study also develops a comprehensive model (OSTAM) by identifying social technology and generational factors as guiding factors that influence the relationship between attitude and intention towards using this technology in improving the performance of educational organizations. Based on the literature review, a research framework was developed that includes a theoretical aspect supported by a questionnaire to test the research hypotheses in this study.